Kidney microRNA Expression Pattern in Type 2 Diabetic Nephropathy in BTBR Ob/Ob Mice - Lucas Opazo-Ríos; Lucas Opazo-Ríos; Antonio Tejera-Muñoz; Manuel Soto Catalan; Vanessa Marchant; Carolina Lavoz; Sebastián Mas Fontao; Juan Antonio Moreno; Marta Fierro Fernandez; Ricardo Ramos; Beatriz Suarez-Alvarez; Carlos López-Larrea; et al. (Frontiers Media S.A., 2022)
Diabetic nephropathy (DN) is the main leading cause of chronic kidney disease worldwide. Although remarkable therapeutic advances have been made during the last few years, there still exists a high residual risk of disease progression to end-stage renal failure. To further understand the pathogenesis of tissue injury in this disease, by means of the Next-Generation Sequencing, we have studied the microRNA (miRNA) differential expression pattern in kidneys of Black and Tan Brachyury (BTBR) ob/ob (leptin deficiency mutation) mouse. This experimental model of type 2 diabetes and obesity recapitulates the key histopathological features described in advanced human DN and therefore can provide potential useful translational information. The miRNA-seq analysis, performed in the renal cortex of 22-week-old BTBR ob/ob mice, pointed out a set of 99 miRNAs significantly increased compared to non-diabetic, non-obese control mice of the same age, whereas no miRNAs were significantly decreased. Among them, miR-802, miR-34a, miR-132, miR-101a, and mir-379 were the most upregulated ones in diabetic kidneys. The in silico prediction of potential targets for the 99 miRNAs highlighted inflammatory and immune processes, as the most relevant pathways, emphasizing the importance of inflammation in the pathogenesis of kidney damage associated to diabetes. Other identified top canonical pathways were adipogenesis (related with ectopic fatty accumulation), necroptosis (an inflammatory and regulated form of cell death), and epithelial-to-mesenchymal transition, the latter supporting the importance of tubular cell phenotype changes in the pathogenesis of DN. These findings could facilitate a better understanding of this complex disease and potentially open new avenues for the design of novel therapeutic approaches to DN.